Studi Literatur Analisis Tingkat Literasi Keuangan Dalam Meningkatkan Perilaku Keuangan Pada Remaja - Hamidah, Ernanda Nur; Subroto, Waspodo Tjipto; Hakim, Luqman (Universitas Pendidikan Ganesha, 2023)
Saving behavior is an action to reduce consumption, that is, individuals can consume it in the future. A bad money management attitude will make it difficult for individuals to save and are afraid to save, it will even make them accustomed to the luxurious lifestyle that constantly occurs in everyday life. It is suspected that the importance of thrifty behavior in adolescents can reduce waste in consumption activities carried out. This research method is a library search or search by library search. In this study it was found that good financial knowledge would be able to increase the saving behavior of young people. Suggestions from this study, it is hoped that financial literacy programs can be improved and integrated into learning materials at various levels of study, in order to improve the right attitude in financial management, namely saving, investing, understanding financial features and services, and even making financial decisions.